Planning for Urban Food Security Using a Spatial Multicriteria Decision-Making Approach - Edrish, Maria Binte (My University, 2026)
Discussions related to healthy food access often overlook the social, environmental and regulatory factors that shape it. Within urban environment, these factors intersect with others to create both opportunities and inequities, shaping the geography of who has access to healthy food and who doesn’t. To develop a resilient urban food system, we need to consider these multidimensional determinants of an urban foodscape. In this study, a place-based decision-support framework is presented, which moves from the identification of priority neighborhoods for improving food access to the recommendation of viable interventions. Using the Kansas City Metropolitan Area as a case study, I quantified the food access Gap by integrating measures of the retail food environment with mobility-based retail activity patterns into an integrated index Integrated Food Access and Environment Index (IFAEI) at the census block group level. In parallel, I construct a neighborhood vulnerability (Need) index using Principal Component Analysis (PCA) and Analytical Hierarchy Process (AHP), incorporating socioeconomic, health, housing, transportation, and demographic dimensions. Bivariate Local Moran’s I is then used to categorize statistically significant local spatial relationships between food accessibility in each Census Block Group (CBG) and vulnerability in neighboring CBGs. I subsequently combine the Vulnerability Index and the IFAEI within each CBG to create a Need-Gap typology, in which high vulnerability indicates high need, and a low IFAEI value indicates a high food-access gap. CBGs where these conditions overlap are classified as High Need-High Gap. To move from diagnosis to action, I examine the highest-priority High Need-High Gap areas using a suitability-screening approach that evaluates local physical, environmental, and regulatory constraints and opportunities for potential food-access interventions. The intervention strategies align with place-based conditions, emphasizing production-oriented strategies where food production is viable and prioritizing distribution-oriented strategies (e.g., farmers’ market sites, pop-up distribution nodes, or candidate locations for healthy retail) in denser areas. Through the suitability screening, I identify candidate sites for project scoping, stakeholder engagement, and future investments. Overall, the study develops a replicable decision support workflow that links equity targeting with feasibility-based siting to generate actionable, locally tailored interventions for building a resilient urban food system.
Keywords: place-based planning; resilience; urban food systems; decision-support system